2010
DOI: 10.1242/jeb.042960
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effects in articular cartilage biomechanics

Abstract: SUMMARYArticular cartilage is the soft tissue that covers contacting surfaces of bones in synovial joints. Cartilage is composed of chondrocytes and an extracellular matrix containing numerous biopolymers, cations and water. Healthy cartilage functions biomechanically to provide smooth and stable joint movement. Degenerative joint diseases such as osteoarthritis involve cartilage deterioration, resulting in painful and cumbersome joint motion. Temperature is a fundamental quantity in mechanics, yet the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Literature indicates no change in mechanical properties for articular cartilage between 20°C and 37°C (June and Fyhrie, 2010), and room temperature is routinely used (Mow et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Literature indicates no change in mechanical properties for articular cartilage between 20°C and 37°C (June and Fyhrie, 2010), and room temperature is routinely used (Mow et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…In the compressive experiment, the specimen was also kept in well water-soaked condition of PBS solution throughout the experiment to maintain hydration and osmotic phenomena. The compressive experiment and reservation state between experiments were executed in air-conditionated room temperature of 23°C, in which it was reported that articular cartilage drastically changes mechanical stiffness by exposing to around 60°C (June et al, 2010).…”
Section: Experimental Apparatus and Materialsmentioning
confidence: 99%
“…By advance of experimental apparatus, several experimental reports especially emphasized the importance of the high-speed compression, e.g. walking condition (June and Fyhrie, 2010;Espino et al, 2014). We should note that 3-dimensional FE model is also one of the physiological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Although water is the most abundant NC component, only a small portion is tightly bounded to the matrix. Thus, water within cartilaginous structures can be separated into fibrillar and intrafibrillar volumes [38]. Cartilage's affinity for water is primarily justified by the presence of significant quantities of PGs, whose negative side chain charges attract free positive ions and increase internal osmotic pressure [39,40].…”
Section: Introductionmentioning
confidence: 99%